That one should disdain hardships : the teachings of a Roman Stoic - Musonius Rufus, C. (Caius), approximately 30-; Lutz, Cora E. (Cora Elizabeth), 1906-1985; Reydams-Schils, Gretchen J. (New Haven : Yale University Press, 2020)
Perennial wisdom from one of history's most important Stoic teachers The Stoic philosopher Musonius Rufus was one of the most influential teachers of his era, imperial Rome, and his message still resonates with startling clarity today. Alongside Stoics like Seneca, Epictetus, and Marcus Aurelius, he emphasized ethics in action, displayed in all aspects of life. Merely learning philosophical doctrine and listening to lectures, they believed, will not do one any good unless one manages to interiorize the teachings and apply them to daily life. In Musonius Rufus's words, "Philosophy is nothing else than to search out by reason what is right and proper and by deeds to put it into practice." At a time of renewed interest in Stoicism, this collection of Musonius Rufus's lectures and sayings, beautifully translated by Cora E. Lutz and introduced by Gretchen Reydams-Schils, offers readers access to the thought of one of history's most influential and remarkable Stoic thinkers.
Frontmatter -- Contents -- Introduction -- A Note on the Translation -- 1. That There Is No Need of Giving Many Proofs for One Problem -- 2. That Man Is Born with an Inclination Toward Virtue -- 3. That Women Too Should Study Philosophy -- 4. Should Daughters Receive the Same Education as Sons? -- 5. Which Is More Effective, Theory or Practice? -- 6. On Training -- 7. That One Should Disdain Hardships -- 8. That Kings Also Should Study Philosophy -- 9. That Exile Is Not an Evil -- 10. Will the Philosopher Prosecute Anyone for Personal Injury? -- 11. What Means of Livelihood Is Appropriate for a Philosopher? -- 12. On Sexual Indulgence -- 13. What Is the Chief End of Marriage? -- 14. Is Marriage a Handicap for the Pursuit of Philosophy? -- 15. Should Every Child That Is Born Be Raised? -- 16. Must One Obey One's Parents Under All Circumstances? -- 17. What Is the Best Viaticum for Old Age? -- 18. On Food -- 19. On Clothing and Shelter -- 20. On Furnishings -- 21. On Cutting the Hair -- 22-53. Fragments -- Sources of the Text -- Further Reading
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Conduct of life -- Early works to 1800.; Ethics -- Early works to 1800.; Stoics; Morale pratique -- Ouvrages avant 1800.; Morale -- Ouvrages avant 1800.; Stoïcisme.; stoicism; PHILOSOPHY -- Ethics & Moral Philosophy; Conduct of life; Ethics; Stoics; Early works